Answer:
A sample space is a collection or a set of possible outcomes of a random experiment. The sample space is represented using the symbol, “S”. The subset of possible outcomes of an experiment is called events. A sample space may contain a number of outcomes that depends on the experiment
Hope this helps even a little bit:)
Looks like the given limit is
![\displaystyle \lim_{n\to\infty} \left(\frac n{3n-1}\right)^{n-1}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Clim_%7Bn%5Cto%5Cinfty%7D%20%5Cleft%28%5Cfrac%20n%7B3n-1%7D%5Cright%29%5E%7Bn-1%7D)
With some simple algebra, we can rewrite
![\dfrac n{3n-1} = \dfrac13 \cdot \dfrac n{n-9} = \dfrac13 \cdot \dfrac{(n-9)+9}{n-9} = \dfrac13 \cdot \left(1 + \dfrac9{n-9}\right)](https://tex.z-dn.net/?f=%5Cdfrac%20n%7B3n-1%7D%20%3D%20%5Cdfrac13%20%5Ccdot%20%5Cdfrac%20n%7Bn-9%7D%20%3D%20%5Cdfrac13%20%5Ccdot%20%5Cdfrac%7B%28n-9%29%2B9%7D%7Bn-9%7D%20%3D%20%5Cdfrac13%20%5Ccdot%20%5Cleft%281%20%2B%20%5Cdfrac9%7Bn-9%7D%5Cright%29)
then distribute the limit over the product,
![\displaystyle \lim_{n\to\infty} \left(\frac n{3n-1}\right)^{n-1} = \lim_{n\to\infty}\left(\dfrac13\right)^{n-1} \cdot \lim_{n\to\infty}\left(1+\dfrac9{n-9}\right)^{n-1}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Clim_%7Bn%5Cto%5Cinfty%7D%20%5Cleft%28%5Cfrac%20n%7B3n-1%7D%5Cright%29%5E%7Bn-1%7D%20%3D%20%5Clim_%7Bn%5Cto%5Cinfty%7D%5Cleft%28%5Cdfrac13%5Cright%29%5E%7Bn-1%7D%20%5Ccdot%20%5Clim_%7Bn%5Cto%5Cinfty%7D%5Cleft%281%2B%5Cdfrac9%7Bn-9%7D%5Cright%29%5E%7Bn-1%7D)
The first limit is 0, since 1/3ⁿ is a positive, decreasing sequence. But before claiming the overall limit is also 0, we need to show that the second limit is also finite.
For the second limit, recall the definition of the constant, <em>e</em> :
![\displaystyle e = \lim_{n\to\infty} \left(1+\frac1n\right)^n](https://tex.z-dn.net/?f=%5Cdisplaystyle%20e%20%3D%20%5Clim_%7Bn%5Cto%5Cinfty%7D%20%5Cleft%281%2B%5Cfrac1n%5Cright%29%5En)
To make our limit resemble this one more closely, make a substitution; replace 9/(<em>n</em> - 9) with 1/<em>m</em>, so that
![\dfrac{9}{n-9} = \dfrac1m \implies 9m = n-9 \implies 9m+8 = n-1](https://tex.z-dn.net/?f=%5Cdfrac%7B9%7D%7Bn-9%7D%20%3D%20%5Cdfrac1m%20%5Cimplies%209m%20%3D%20n-9%20%5Cimplies%209m%2B8%20%3D%20n-1)
From the relation 9<em>m</em> = <em>n</em> - 9, we see that <em>m</em> also approaches infinity as <em>n</em> approaches infinity. So, the second limit is rewritten as
![\displaystyle\lim_{n\to\infty}\left(1+\dfrac9{n-9}\right)^{n-1} = \lim_{m\to\infty}\left(1+\dfrac1m\right)^{9m+8}](https://tex.z-dn.net/?f=%5Cdisplaystyle%5Clim_%7Bn%5Cto%5Cinfty%7D%5Cleft%281%2B%5Cdfrac9%7Bn-9%7D%5Cright%29%5E%7Bn-1%7D%20%3D%20%5Clim_%7Bm%5Cto%5Cinfty%7D%5Cleft%281%2B%5Cdfrac1m%5Cright%29%5E%7B9m%2B8%7D)
Now we apply some more properties of multiplication and limits:
![\displaystyle \lim_{m\to\infty}\left(1+\dfrac1m\right)^{9m+8} = \lim_{m\to\infty}\left(1+\dfrac1m\right)^{9m} \cdot \lim_{m\to\infty}\left(1+\dfrac1m\right)^8 \\\\ = \lim_{m\to\infty}\left(\left(1+\dfrac1m\right)^m\right)^9 \cdot \left(\lim_{m\to\infty}\left(1+\dfrac1m\right)\right)^8 \\\\ = \left(\lim_{m\to\infty}\left(1+\dfrac1m\right)^m\right)^9 \cdot \left(\lim_{m\to\infty}\left(1+\dfrac1m\right)\right)^8 \\\\ = e^9 \cdot 1^8 = e^9](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Clim_%7Bm%5Cto%5Cinfty%7D%5Cleft%281%2B%5Cdfrac1m%5Cright%29%5E%7B9m%2B8%7D%20%3D%20%5Clim_%7Bm%5Cto%5Cinfty%7D%5Cleft%281%2B%5Cdfrac1m%5Cright%29%5E%7B9m%7D%20%5Ccdot%20%5Clim_%7Bm%5Cto%5Cinfty%7D%5Cleft%281%2B%5Cdfrac1m%5Cright%29%5E8%20%5C%5C%5C%5C%20%3D%20%5Clim_%7Bm%5Cto%5Cinfty%7D%5Cleft%28%5Cleft%281%2B%5Cdfrac1m%5Cright%29%5Em%5Cright%29%5E9%20%5Ccdot%20%5Cleft%28%5Clim_%7Bm%5Cto%5Cinfty%7D%5Cleft%281%2B%5Cdfrac1m%5Cright%29%5Cright%29%5E8%20%5C%5C%5C%5C%20%3D%20%5Cleft%28%5Clim_%7Bm%5Cto%5Cinfty%7D%5Cleft%281%2B%5Cdfrac1m%5Cright%29%5Em%5Cright%29%5E9%20%5Ccdot%20%5Cleft%28%5Clim_%7Bm%5Cto%5Cinfty%7D%5Cleft%281%2B%5Cdfrac1m%5Cright%29%5Cright%29%5E8%20%5C%5C%5C%5C%20%3D%20e%5E9%20%5Ccdot%201%5E8%20%3D%20e%5E9)
So, the overall limit is indeed 0:
![\displaystyle \lim_{n\to\infty} \left(\frac n{3n-1}\right)^{n-1} = \underbrace{\lim_{n\to\infty}\left(\dfrac13\right)^{n-1}}_0 \cdot \underbrace{\lim_{n\to\infty}\left(1+\dfrac9{n-9}\right)^{n-1}}_{e^9} = \boxed{0}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Clim_%7Bn%5Cto%5Cinfty%7D%20%5Cleft%28%5Cfrac%20n%7B3n-1%7D%5Cright%29%5E%7Bn-1%7D%20%3D%20%5Cunderbrace%7B%5Clim_%7Bn%5Cto%5Cinfty%7D%5Cleft%28%5Cdfrac13%5Cright%29%5E%7Bn-1%7D%7D_0%20%5Ccdot%20%5Cunderbrace%7B%5Clim_%7Bn%5Cto%5Cinfty%7D%5Cleft%281%2B%5Cdfrac9%7Bn-9%7D%5Cright%29%5E%7Bn-1%7D%7D_%7Be%5E9%7D%20%3D%20%5Cboxed%7B0%7D)
The quotient, or resulting number, will decrease.
Answer:
There is no question showing up so I dont know how to help u
Step-by-step explanation: